Firm growth: a survey - Alexander Coad (Max Planck Institute of Economics, 2007)
We survey the phenomenon of the growth of firms drawing on literature from economics, management, and sociology. We begin with a review of empirical 'stylised facts' before discussing theoretical contributions. Firm growth is characterized by a predominant stochastic element, making it difficult to predict. Indeed, previous empirical research into the determinants of firm growth has had a limited success. We also observe that theoretical propositions concerning the growth of firms are often amiss. We conclude that progress in this area requires solid empirical work, perhaps making use of novel statistical techniques.
Keywords: L25; L11; 330; Firm Growth; Size Distribution; Growth Rates Distribution; Gibrat's Law; Theory of the Firm; Diversification; 'Stages of Growth' models; Unternehmenswachstum; Unternehmensentwicklung; Empirische Methode; Theorie